(3QSGdI aj eYQaI CeQGV GdYjf hCSHGHgGs - (3YjSi Hf Ydj, GdeJWHHs ((3jhSa Hf eMeO Hf jhSa s)
(3ChdgG (B:s
(3hUd cJGHc CjgG GdCN GdaGVd JSCd ajg Yf LhGeY cJH LGdjfhS ai CeQGV GdYjf hCSHGHgG hYdGeGJgG s
(3BNQgG (B:s
(3agPg LedI GdCOhjI GdJi JSJYed ai YdGL Ydd GdYjf hbO HdZJ dc eG SCdJ hCf JLYd ecCaGJi Ydi bVGA MGLJc cKQI GdOYGA JeJ GdebGdI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(1569) s
Keywords: (3GdWHs